The Idea of the Digital State in the Face of the Russian Cultural Tradition of Understanding of Sense of the Government - V. В. Aleksandrov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
In article comparison of the idea of the digital state understood as the platform on which the system of services, with understanding of the state in the Russian cultural tradition is created is carried out. It is believed that an adequate reflection at the philosophical level of this tradition is represented in the works of Russian thinkers who argued that the task of state power should be to assert the spiritual unity of the people, and that the solution of this task implies mutual recognition of the spiritual dignity of the power and the person before it. In article the attention to need to avoid “digital euphoria” and importance of constant statement of the decisions made on the basis of “good” technologies before court of those values with which the spiritual dignity of the person is connected is paid.